Dynamic capabilities, preservation of socioemotional wealth, and family firm performance - Felipe Hernández-Perlines; Luis Araya-Castillo; Mercedes Castro Nu\~no (Journal of Innovation & Knowledge (JIK), 2025)
This study examines the performance of family businesses through the theoretical lenses of dynamic capabilities and socioemotional wealth. A conceptual model is proposed, in which socioemotional wealth moderates the relationship between dynamic capabilities and family firm performance. The research employs partial least squares structural equation modeling (PLS-SEM), a second-generation multivariate analysis technique, to analyze data and test hypotheses. The findings reveal that dynamic capabilities positively influence family firm performance, with innovation emerging as the most impactful dynamic capability. Additionally, socioemotional wealth not only directly enhances performance but also acts as a moderator, strengthening the relationship between dynamic capabilities and performance. This study makes two key contributions. First, it advances the understanding of how dynamic capabilities and socioemotional wealth shape family firm performance. Second, it underscores the pivotal role of socioemotional wealth in amplifying the effects of dynamic capabilities on performance. These insights have significant practical implications for family firms, emphasizing the importance of strategically managing both dynamic capabilities and socioemotional wealth to drive performance and ensure long-term sustainability.
Keywords: C88; D21; M21; 650; Family firms; Dynamic capabilities; Socioemotional wealth; Performance